The Origin and Evolution of a Complex Cuspate Foreland: Pointe-aux-Pins, Lake Erie, Ontario - Coakley, J. (Géographie physique et Quaternaire, 1989)
ABSTRACTThe origin of Pointe-aux-Pins, a large, rounded, cuspate foreland protruding from the north shore of Lake Erie, is difficult to explain by conventional spit formation processes. Stratigraphic evidence from boreholes, the distribution of nearshore sediments, surface geomorphology, and previously published interpretations of Lake Erie water levels were combined to produce an hypothetical model of the development of the foreland from approximately 12,000 years BP to now. According to the model, the ancestral Pointe-aux-Pins began as a promontory caused by the intersection of the cross-lake Erieau moraine with the original lake shoreline, then located tens of kilometres lakeward of its present position. Lake levels at the time were about 30 m below present datum (173.3 m a.s.l.). Modern Pointe-aux-Pins dates from after the Nipissing "flood", at about 3500 BP, when the thereto-submerged sandy spit platform was again subjected to wave action, leading to beach ridge and dune formation. The age of the foreland of 3500 to 4000 years compares well with estimates based on the annual sand supply rate and the present sand volume in Pointe-aux-Pins.